Thermocline state change in the eastern equatorial Pacific during the late Pliocene/early Pleistocene intensification of Northern Hemisphere glaciation - Jakob, Kim; Pross, Jörg; Scholz, Christian; Friedrich, Oliver (Climate of the past, 2018)
Abstract. The late Pliocene/early Pleistocene intensification of Northern Hemisphere glaciation (iNHG) ∼ 2.5 million years ago (marine isotope stages, MIS, 100-96) stands out as an important tipping point in Earth's climate history, which strongly influenced oceanographic and climatic patterns including trade wind and upwelling strength in the eastern equatorial Pacific (EEP). The thermocline depth in the EEP, in turn, plays a pivotal role in the Earth's climate system: small changes in its depth associated with short-term climate phenomena such as the El Niño-Southern Oscillation can affect surface-water properties and the ocean-atmosphere exchange. However, thermocline dynamics in the EEP during the iNHG still remain unclear. While numerous studies have suggested a link between a thermocline shoaling in the EEP and Northern Hemisphere ice growth, other studies have indicated a stable thermocline depth during the iNHG; consequently, a causal relationship between thermocline dynamics and ice-sheet growth has been excluded. In light of these contradictory views, we have generated geochemical (planktic foraminiferal δ18O, δ13C and Mg / Ca), sedimentological (sand accumulation rates) and faunal (abundance data of thermocline-dwelling foraminifera) records for Ocean Drilling Program Site 849 located in the central region of the EEP. Our records span the interval from ∼ 2.75 to 2.4 Ma (MIS G7-95), which is critical for understanding thermocline dynamics during the final phase of the iNHG. Our new records document a thermocline shoaling from ∼ 2.64 to 2.55 Ma (MIS G2-101) and a relatively shallow thermocline from ∼ 2.55 Ma onwards (MIS 101-95). This indicates a state change in thermocline depth at Site 849 shortly before the final phase of the iNHG. Ultimately, our data support the hypothesis that (sub-)tropical thermocline shoaling may have contributed to the development of large Northern Hemisphere ice sheets.